Implementasi Teori Dakwah Fungsional dalam Meningkatkan Kesejahteraan Ummat - Uwoh Saefuloh (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
Da’wah is a changing process that orient to change a condition / society life situation to aim condition of its life the better. This mean that Da’i. constitute agent of social change that gets to build condition/ society life situation goodly and welfare. In consequence, in aplicate, da’wah processes ought to use theory and functional da’wah approach. Its mean, theory and also da’wah approach utilized is relevant with charge of society life reality that stipulates with charge of  the lives need. To it Alquran was laid a lot of practical bases dual with da’wah theory implementation which relevant with society reality as mad ’ u  its relationship with ummah well-being step-up.